Brake pad mixture, synthetic brake pad and preparation method and application of synthetic brake pad
By using liquid nitrile rubber, modified phenolic resin and reinforced fibers, and using specific mixing and pressing processes, the problem of poor uniformity of existing gate sheet materials during the mixing process is solved, and the high friction stability and reliability of the synthetic gate sheet is achieved, and the safety and stability of the brake system is improved.
Patent Information
- Application Number
- CN202411799407.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-09
AI Technical Summary
It is difficult for existing shutter sheet materials to ensure the uniformity of the material during the mixing process, resulting in unstable braking performance and the frictional performance of each batch of products vary greatly, which affects the safety and stability of the braking system.
A gate sheet mixture consisting of liquid nitrile rubber, modified phenolic resin and reinforced fiber is used, and through specific mixing and pressing processes, including adjusting the rotation speed of the main paddle and the high-speed paddle, ensuring uniform mixing and bonding of the raw materials.
The friction stability and reliability of the synthetic brake pad is improved, the friction performance differences between batches are reduced, and the safety and stability of the brake system is significantly improved.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of brake friction materials, and in particular to a brake pad mixture, a synthetic brake pad, and a preparation method and application thereof. Background Art
[0002] Brake pad materials are a key component of the vehicle braking system, directly affecting the braking performance and service life. With the rapid development of rail transit technology, brake pad materials face more stringent working conditions, requiring good wear resistance, heat resistance and braking stability, while also considering factors such as cost and environmental protection. The research and development of high-performance brake pad materials is crucial to improving the reliability and safety of train braking systems.
[0003] Existing brake pad materials mainly include rubber-based composite materials, which improve the comprehensive performance of materials by mixing different components. Common components include various rubbers, reinforcing fibers, fillers, etc. However, the brake pad preparation processes currently available on the market often find it difficult to ensure the uniformity of materials or the material properties are prone to change during the mixing process. For example, dry mixing mixes the mixture without pressurization, and the mixing time is short, but the mixture is fluffy and has poor uniformity; internal mixing uses an internal mixer to mix the mixture evenly at a certain speed and pressure. During the process, the mixture will generate heat through friction, causing the organic components in the mixture to undergo chemical reactions, resulting in unstable quality of the brake pad products and large differences in friction performance between batches of products, affecting the safety and stability of the entire brake system.
[0004] Therefore, it is urgent to develop a new brake pad material and preparation method to prepare a synthetic brake pad with good internal uniformity, good friction stability and reliability, and small batch-to-batch difference. Summary of the invention
[0005] In order to improve the friction stability and reliability of a synthetic brake pad, the present application provides a brake pad mixture, a synthetic brake pad, and a preparation method and application thereof.
[0006] In the first aspect, the present application provides a brake pad mixture, which adopts the following technical solution: A brake pad mixture, comprising the following components in parts by weight: 10-13 parts of liquid nitrile rubber, 8-12 parts of modified phenolic resin, 20-40 parts of reinforcing fiber, 8-12 parts of calcium hydroxide, 1-3 parts of light magnesium oxide, 10-15 parts of calcium carbonate whiskers, 2-5 parts of calcined alumina, 10-15 parts of graphite, 5-10 parts of heavy calcium carbonate, 0.8-1.2 parts of sulfur, and 0.8-1.2 parts of accelerator; The reinforcing fibers include steel fibers, aramid fibers and mineral fibers in a weight ratio of (10-25):1:(5-15).
[0007] The present application adopts liquid nitrile rubber, modified phenolic resin and reinforcing fiber to prepare a brake pad mixture. The brake pad prepared by the brake pad mixture has good mechanical properties, excellent heat resistance and wear resistance, and is suitable for various vehicle braking systems, effectively improving braking safety and reliability. Specifically, the present application adopts steel fiber, aramid fiber and mineral fiber with a weight ratio of (10-25):1:(5-15) as reinforcing fiber. The reinforcing fiber has good mixing uniformity with liquid nitrile rubber, modified phenolic resin and filler, which can effectively improve the overall mechanical strength and friction performance of the brake pad mixture, making the friction performance of the brake pad more stable. In addition, the presence of liquid nitrile rubber and modified phenolic resin not only ensures the good bonding performance of the material and its excellent bonding force to the metal matrix, but also effectively improves the dimensional stability of the brake pad under high temperature working conditions. The use of fillers such as light magnesium oxide and calcium carbonate whiskers can optimize the friction coefficient of the material, making it more uniform and stable, thereby significantly reducing the noise and vibration during braking and extending the service life of the brake pad.
[0008] Optionally, the weight ratio of the steel fiber, aramid fiber and mineral fiber is (15-20):1:(8-12).
[0009] In some embodiments, the weight ratio of the steel fiber, aramid fiber and mineral fiber can be (10-15):1:10, (10-20):1:10, (10-25):1:10, (15-20):1:10, (15-25):1:10, (20-25):1:10, 20:1:(5-8), 20:1:(5-10), 20:1:(5-12), 20:1:(5-15), 20:1:(8-10), 20:1:(8-12), 20:1:(8-15), 20:1:(10-12), 20:1:(10-15) or 20:1:(12-15).
[0010] In a specific embodiment, the weight ratio of the steel fiber, the aramid fiber and the mineral fiber can also be 10:1:10, 15:1:10, 20:1:10, 25:1:10, 20:1:5, 20:1:8 or 20:1:15.
[0011] Optionally, the steel fiber has a diameter of 0.05±0.01 mm and an aspect ratio of 25-35.
[0012] Optionally, the fineness of the calcined alumina is 2500-3500 mesh, the fineness of the calcium hydroxide is 300-350 mesh, and the fineness of the graphite is 80-120 mesh.
[0013] In a second aspect, the present application provides a composite brake pad.
[0014] In a third aspect, the present application provides a method for preparing a composite brake pad.
[0015] A method for preparing a synthetic brake pad comprises the following steps: Mixing: First, put the reinforcing fiber, calcium hydroxide, light magnesium oxide, calcium carbonate whisker, calcined alumina, graphite, heavy calcium carbonate, sulfur and accelerator into the mixing equipment, adjust the main propeller speed v1 to 140-160rpm, the high-speed propeller speed V to 1500-1900rpm, and mix for 3-4 minutes; then inject liquid nitrile rubber and modified phenolic resin into the mixer, mix for 3-4 minutes, and obtain the brake pad mixture; Pressing: Press the brake pad mixture at 80-100℃ and 50-65bar for 200-360s to make a brake pad preform; Curing: Curing the brake pad preform to obtain a composite brake pad.
[0016] The present application provides a method for preparing a synthetic brake pad. The method controls the stirring speeds of the main slurry and the high-speed slurry within the above-mentioned range, thereby improving the mixing uniformity of the raw materials, making the friction performance of the synthetic brake pads produced between batches less different and the product stability better.
[0017] In some embodiments, the main propeller rotation speed v1 may be 140-150 rpm or 150-160 rpm.
[0018] In a specific embodiment, the main propeller rotation speed v1 can also be 140 rpm, 150 rpm or 160 rpm.
[0019] In some embodiments, the high-speed paddle rotation speed V may be 1500-1700 rpm or 1700-1900 rpm.
[0020] In a specific embodiment, the high-speed paddle rotation speed V can also be 1500 rpm, 1700 rpm or 1900 rpm.
[0021] Optionally, the feeding time of the liquid nitrile rubber and the modified phenolic resin is controlled within 1 minute.
[0022] Optionally, the curing temperature is 210-220° C. and the curing time is 6-8 hours.
[0023] Optionally, after the liquid nitrile rubber and modified phenolic resin are added, the main propeller speed v2 needs to be adjusted to 170-190r / min.
[0024] In some embodiments, the main propeller speed v2 can be 150-170rpm, 150-180rpm, 150-190rpm, 150-220rpm, 170-180rpm, 170-190rpm, 170-220rpm, 180-190rpm, 180-220rpm or 190-220rpm.
[0025] In a specific embodiment, the main propeller rotation speed v2 can also be 150 rpm, 170 rpm, 180 rpm, 190 rpm or 220 rpm.
[0026] In a fourth aspect, the brake pad mixture, synthetic brake pad and synthetic brake pad preparation method provided in the present application are used in a vehicle braking system.
[0027] In summary, this application has the following beneficial effects: 1. The present application uses liquid nitrile rubber, modified phenolic resin, reinforcing fiber and calcium hydroxide as raw materials to prepare a synthetic brake pad, and uses steel fiber, aramid fiber and mineral fiber in a weight ratio of (10-25):1:(5-15) as reinforcing fiber. The obtained synthetic brake pad has excellent friction and friction stability, and has good safety and reliability when used in the braking system of traffic vehicles.
[0028] 2. The present application further controls the weight ratio of steel fiber, aramid fiber and mineral fiber in the reinforcing fiber within the range of (15-20):1:(8-12), and the obtained synthetic brake pad has better wear resistance and smaller friction difference between batches.
[0029] 3. The present application improves the uniformity of the mixture by adjusting the main slurry rotation speed and the high-speed paddle rotation speed in the preparation method of the synthetic brake pad, thereby improving the quality stability of the synthetic brake pad and solving the problem of inconsistent friction performance of synthetic brake pads between batches in the related art. DETAILED DESCRIPTION
[0030] The present application provides a brake pad mixture, comprising the following components in parts by weight: 10-13 parts of liquid nitrile rubber, 8-12 parts of modified phenolic resin, 20-40 parts of reinforcing fiber, 8-12 parts of calcium hydroxide, 1-3 parts of light magnesium oxide, 10-15 parts of calcium carbonate whisker, 2-5 parts of calcined alumina, 10-15 parts of graphite, 5-10 parts of heavy calcium carbonate, 0.8-1.2 parts of sulfur, and 0.8-1.2 parts of accelerator; the reinforcing fiber comprises steel fiber, aramid fiber and mineral fiber in a weight ratio of (10-25):1:(5-15). Further, the weight ratio of the steel fiber, aramid fiber and mineral fiber is (15-20):1:(8-12).
[0031] Wherein, the diameter of the steel fiber is 0.05±0.01 mm, and the aspect ratio is 25-35; the fineness of the calcined alumina is 2500-3500 mesh, the fineness of the calcium hydroxide is 300-350 mesh, and the fineness of the graphite is 80-120 mesh.
[0032] The method for preparing the composite brake pad provided in the present application is characterized by comprising the following steps: (1) Mixing: Put reinforcing fiber, calcium hydroxide, light magnesium oxide, calcium carbonate whisker, calcined alumina, graphite, heavy calcium carbonate, sulfur and accelerator into a vacuum mixer, adjust the main propeller speed to 140-160 rpm, the high-speed propeller speed to 1500-1900 rpm, and mix for 3-4 minutes; then inject liquid nitrile rubber and modified phenolic resin into the mixer through the atomizing pouring port of the mixer within 1 minute, and increase the main propeller speed to 170-190 r / min. After mixing for 3-4 minutes, a brake pad mixture is obtained.
[0033] (2) Pressing: The brake pad mixture is pressed using a proportional press at 80-100° C. and a pressing pressure of 50-65 bar for 200-360 seconds to form a brake pad preform.
[0034] (3) Curing: Curing the brake pad preform at 210-220° C. for 6-8 hours to obtain a synthetic brake pad.
[0035] In the present application, the model of liquid nitrile rubber is LNBR-827XE; the model of modified phenolic resin is PF2184; the diameter of steel fiber is 0.05 mm and the aspect ratio is 20; the model of aramid fiber is HP100; the model of mineral fiber is RB250; the model of lightweight magnesium oxide is 93C-BL; the fineness of calcium hydroxide is 325 mesh; the model of calcium carbonate whisker is NP-M02; the fineness of calcined alumina is 3000 mesh, purchased from Hangzhou Xiaoshan Great Wall Aluminum Materials Co., Ltd.; the fineness of graphite is 100 mesh, purchased from Qingdao Chenglong Graphite Co., Ltd.; the fineness of heavy calcium carbonate is 325 mesh, purchased from Nanyang Fuxiang Calcium Carbonate; the model of accelerator is DM; the raw materials, reagents, solvents, etc. used in this application can all be obtained commercially.
[0036] The present application is further described in detail below in conjunction with embodiments and performance testing experiments.
[0037] Examples 1-8 Embodiments 1-8 each provide a composite brake pad.
[0038] The difference between the above embodiments is that the ratio of each component in the reinforcing fiber is specifically shown in Table 1 below.
[0039] The method for preparing the synthetic brake pad provided in Examples 1-8 comprises the following steps: (1) Mixing: reinforcing fiber, calcium hydroxide, light magnesium oxide, calcium carbonate whisker, calcined alumina, graphite, heavy calcium carbonate, sulfur and accelerator are put into a vacuum mixer, the main propeller speed v1 is adjusted to 150 rpm, the high-speed propeller speed V is adjusted to 1700 rpm, and mixing is carried out for 3 min; then, liquid nitrile rubber and modified phenolic resin are injected into the mixer through the atomizing pouring port of the mixer within 1 min, and the main propeller speed v2 is increased to 180 r / min. After mixing for 3 min, a brake pad mixture is obtained.
[0040] (2) Pressing: The brake pad mixture is pressed using a proportional press at 90° C. and a pressing pressure of 60 bar for 240 seconds to form a brake pad preform.
[0041] (3) Curing: The brake pad preform was cured at 220° C. for 8 h to obtain a synthetic brake pad.
[0042] Table 1 Weight ratio of each component of the reinforcing fiber in the synthetic brake pad provided by Examples 1-8 Example Weight ratio of steel fiber, aramid fiber and mineral fiber 1 10:1:10 2 15:1:10 3 20:1:10 4 25:1:10 5 20:1:5 6 20:1:8 7 20:1:12 8 20:1:15 Examples 9-16 Embodiments 9-16 each provide a composite brake pad.
[0043] The difference between the above embodiment and embodiment 3 is that the rotation speed in the mixing step is specifically shown in Table 2 below.
[0044] Table 2 Rotation speed in the mixing step of the preparation method of Example 3, Example 9-16 Comparative Example 1 Comparative Example 1 provides a synthetic brake pad.
[0045] The difference between the comparative example and Example 3 is that the reinforcing fibers include steel fibers, aramid fibers and mineral fibers in a weight ratio of 1:1:1.
[0046] Comparative Example 2 Comparative Example 2 provides a synthetic brake pad.
[0047] The difference between the comparative example and Example 3 is that the reinforcing fibers include steel fibers, aramid fibers and mineral fibers in a weight ratio of 5:1:5.
[0048] Comparative Example 3 Comparative Example 3 provides a synthetic brake pad.
[0049] The difference between the comparative example and Example 3 is that the main propeller rotation speed v1 is 100 rpm and the high-speed propeller rotation speed V is 1300 rpm.
[0050] Comparative Example 4 Comparative Example 4 provides a synthetic brake pad.
[0051] The difference between the comparative example 4 and the embodiment 3 is: the preparation method of the synthetic brake pad.
[0052] The preparation method of the synthetic brake pad provided in Comparative Example 4 comprises the following steps: 1. Mixing: Put liquid nitrile rubber, modified phenolic resin, reinforcing fiber, calcium hydroxide, light magnesium oxide, calcium carbonate whisker, calcined alumina, graphite, heavy calcium carbonate, sulfur and accelerator into a vacuum mixer, adjust the main propeller speed v1 to 150rpm, the high-speed propeller speed V to 1700rpm, mix for 5 minutes, and obtain the brake pad mixture.
[0053] (2) Pressing: The brake pad mixture is pressed using a proportional press at 90° C. and a pressing pressure of 60 bar for 240 seconds to form a brake pad preform.
[0054] (3) Curing: The brake pad preform was cured at 220° C. for 8 h to obtain a synthetic brake pad.
[0055] Performance testing The friction performance stability test was carried out on the synthetic brake pads prepared in Examples 1-16 and Comparative Examples 1-4, and the test results are shown in Table 3 below: Friction stability experiment: The synthetic brake pads were subjected to emergency braking at 120 km / h to test the friction coefficient of the synthetic brake pads; the friction coefficients of 5 batches were tested in parallel, and the relative standard deviation RSD values of the 5 groups of data were calculated.
[0056] Note: When emergency braking is performed at 120km / h, the friction coefficient of the brake pad is required to be 0.310-0.406 The smaller the relative standard deviation (RSD) value, the smaller the batch-to-batch difference of the synthetic brake pad and the better the friction stability.
[0057] Table 3 Friction stability test results of synthetic brake pads of Examples 1-16 and Comparative Examples 1-4 According to the test results in Table 3, the average friction coefficient of the synthetic brake pads obtained in Examples 1-16 of the present application is 0.354-0.360, and the RSD values of the friction coefficients of the five batches of products are 0.38-0.69%. This indicates that the brake pad mixture and the preparation method of the synthetic brake pad provided in the present application can prepare a synthetic brake pad with good uniformity and good quality stability, and the use of the brake pad in the vehicle braking system can meet the safety and reliability requirements.
[0058] The test results of Examples 1-8 and Comparative Examples 1-2 show that Example 1-8 uses steel fiber, aramid fiber and mineral fiber in a weight ratio of (10-25):1:(5-15) as reinforcing fiber, and the reinforcing fiber is mixed evenly with the components in the brake pad mixture, and the quality stability of the obtained synthetic brake pad is good. The average friction coefficient of the synthetic brake pad is 0.354-0.360, and the RSD value of the friction coefficient of 5 batches of products is 0.39-0.69%; while when Comparative Example 1-2 uses steel fiber, aramid fiber and mineral fiber in a weight ratio of 1:1:1 or steel fiber, aramid fiber and mineral fiber in a weight ratio of 5:1:5 as reinforcing fiber, the wrapping and bonding effect between the reinforcing fiber and the rubber, resin and various fillers is poor, so that the internal uniformity of the synthetic brake pad is poor, resulting in poor quality stability of the synthetic brake pad, and the RSD value of the friction coefficient of 5 batches of products is as high as 1.81-2.58%. Therefore, it is shown that the present application uses steel fiber, aramid fiber and mineral fiber in a weight ratio of (10-25):1:(5-15) as reinforcing fibers to prepare a synthetic brake pad with good friction stability.
[0059] Further comparison of Examples 1-8 revealed that the friction coefficient RSD values of the five batches of synthetic brake pads obtained in Examples 2-3, 6-7 were 0.39-047% (≤0.5%), while the friction coefficient RSD values of the five batches of synthetic brake pads obtained in Examples 1, 4-5, and 8 were 0.52-0.69%. Therefore, it is shown that the present application further uses steel fiber, aramid fiber and mineral fiber in a weight ratio of (15-20):1:(8-12) as reinforcing fibers, and the friction stability of the synthetic brake pads obtained is better.
[0060] From the test results of Example 3, Examples 9-16, and Comparative Examples 3-4, it can be seen that in Example 3 and Example 9-16, by adjusting the order of adding the raw materials, and controlling the main paddle speed v1 of the mixing process within the range of 140-160rpm, and the high-speed paddle speed V within the range of 1500-1900rpm, the average friction coefficient of the obtained synthetic brake pad is 0.356-0.360, and the RSD value of the friction coefficient of 5 batches of products is 0.39-0.78%; while in Comparative Example 3, the main paddle speed v1 of the mixing process is controlled within the range of 100rpm, and the high-speed paddle speed V is controlled within the range of 1300rpm, and the average friction coefficient of the obtained synthetic brake pad is 0.357, and the RSD value of the friction coefficient of 5 batches of products is as high as 2.80%; and in Comparative Example 4, all the raw materials are directly mixed at one time, and the average friction coefficient of the obtained synthetic brake pad is 0.353, and the RSD value of the friction coefficient of 5 batches of products is as high as 3.87%. Therefore, the present application explains that the order of adding each raw material is adjusted as follows: reinforcing fiber and each filler are added first, and liquid nitrile rubber and modified phenolic resin are added later, and the main propeller speed v1 of the mixing process is controlled within the range of 140-160rpm, and the high-speed propeller speed V is controlled within the range of 1500-1900rpm, so that the materials of the synthetic brake pad can be fully and evenly mixed, thereby greatly improving the quality stability of the synthetic brake pad. Further comparison of the test results of Example 3 and Examples 13-16 shows that with the increase of the main propeller speed v2, the friction coefficient RSD value of the obtained synthetic brake pad 5 batch products shows a trend of first decreasing and then remaining basically unchanged; among them, when Example 13 sets the main propeller speed v1 and the main propeller speed v2 to 150rpm, the friction coefficient RSD value of the obtained synthetic brake pad 5 batch products is 0.78% (>0.5%); and the friction coefficient RSD value of the synthetic brake pad 5 batch products obtained in Examples 3 and Examples 14-16 is 0.39-0.48% (≤0.5%). Therefore, taking comprehensive cost considerations into account, the present application further controls the main propeller speed v2 within the range of 170-190rpm, so that the obtained synthetic brake pads have better uniformity, the friction performance differences between batches of the obtained synthetic brake pads are small, and the product stability is better.
[0061] Although the present invention has been described in detail above with general descriptions and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements may be made thereto based on the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.
Claims
1. A brake pad mixture, characterized in that: The invention comprises the following components in parts by weight: 10-13 parts of liquid nitrile rubber, 8-12 parts of modified phenolic resin, 20-40 parts of reinforcing fiber, 8-12 parts of calcium hydroxide, 1-3 parts of light magnesium oxide, 10-15 parts of calcium carbonate whisker, 2-5 parts of calcined aluminum oxide, 10-15 parts of graphite, 5-10 parts of heavy calcium carbonate, 0.8-1.2 parts of sulfur and 0.8-1.2 parts of accelerator; The reinforcing fibers include steel fibers, aramid fibers and mineral fibers in a weight ratio of (10-25):1:(5-15).
2. The brake pad mixture according to claim 1, characterized in that: The weight ratio of the steel fiber, aramid fiber and mineral fiber is (15-20):1:(8-12).
3. The brake pad mixture according to claim 1, characterized in that: The diameter of the steel fiber is 0.05±0.01 mm, and the aspect ratio is 25-35.
4. The brake pad mixture according to any one of claims 1 to 3, characterized in that: The fineness of the calcined alumina is 2500-3500 mesh, the fineness of the calcium hydroxide is 300-350 mesh, and the fineness of the graphite is 80-120 mesh.
5. A synthetic brake pad, characterized in that: The brake pad is made of the brake pad mixture according to any one of claims 1 to 4.
6. The method for preparing a composite brake pad according to claim 5, characterized in that: The following steps are involved: Mixing: First, put the reinforcing fiber, calcium hydroxide, light magnesium oxide, calcium carbonate whisker, calcined alumina, graphite, heavy calcium carbonate, sulfur and accelerator into the mixing equipment, adjust the main propeller speed v1 to 140-160rpm, the high-speed propeller speed V to 1500-1900 rpm, and mix for 3-4 minutes; then inject liquid nitrile rubber and modified phenolic resin into the mixer, mix for 3-4 minutes, and obtain the brake pad mixture; Pressing: Press the brake pad mixture at 80-100℃ and 50-65bar for 200-360s to make a brake pad preform; Curing: Curing the brake pad preform to obtain a composite brake pad.
7. The method for preparing a brake pad mixture according to claim 6, characterized in that: The feeding time of the liquid nitrile rubber and the modified phenolic resin is controlled within 1 minute.
8. The method for preparing a brake pad mixture according to claim 6, characterized in that: The curing temperature is 210-220° C. and the curing time is 6-8 hours.
9. The method for preparing a brake pad mixture according to claim 6, characterized in that: After the liquid nitrile rubber and modified phenolic resin are added, the main propeller speed v2 needs to be adjusted to 170-190r / min.
10. Use of the brake pad mixture according to any one of claims 1 to 4, the synthetic brake pad according to claim 5, and a synthetic brake pad obtained by the preparation method of the synthetic brake pad according to any one of claims 6 to 9 in a vehicle braking system.
Citation Information
Patent Citations
Method for preparing brake pad of car by utilizing liquid nitrile rubber
CN101725655A
Calcium carbonate whisker reinforced resin-rubber base friction material and preparation method therefor
CN105111675A
Heavy-metal-free friction material and brake pad
CN105524316A
Brake pad of electric bicycle or motorcycle and preparation method of brake pad
CN106594132A
Environment-friendly friction material and brake pad and preparation method based on environment-friendly friction material
CN110242691A
Cited By
High-temperature-resistant thermosetting synthetic brake lining material and preparation method thereof
CN120248455A